CONSTRUCTIVE JOURNALISM: WHETHER IT IS TIME FOR THE PROBLEM-FOCUSED REPORTING MODEL TO BE REPLACED BY A WALFARE-FOCUSED REPORTING MODEL? - Delić, Amela (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2022)
Since 2015, the phenomenon of constructive journalism has been mentioned in communication theory and practice. Theorists agree that this is a novelty approach of journalism, but there are still terminological doubts when it comes to the precise conceptualization of this direction. Constructive journalism is identified as a direction, a tool, a form, a kind, a concept, as a new philosophy or culture of news. In this paper, we made a metatheoretical analysis of available scientific, qualitative and quantitative research on the concept of constructive journalism. We offered a unique definition, characteristics, role, basic principles, specifics in relation to other journalistic directions and the historical development of constructive journalism. We introduced constructive journalism as a new type or concept of reporting focused on a positive interpretive framework imbued with optimism in which the journalist acts proactively and goes beyond presenting an existing problem. In this journalism type, journalist try to discover possible solutions and examples of good answers to a problem that have already been successfully implemented somewhere, and could be imitated in a specific social context in the present or the future, and in that way answers to the question What to do next. Ultimately, it contributes to the creation of a new culture of news in which the interpretative framework is definitely changing, but media reporting agenda remains the same. The second part of the paper presents results of empirical research obtained by the methods of quantitative content analysis and examination using the written survey technique. The analysis of the content of the Bosnian media (N=663) showed that journalism in Bosnia and Herzegovina is dominated by the classic problem-focused model of reporting with a focus on conflict and negativity as the dominant values ​​of the news. In their answers, citizens (N=445) have shown that they prefer some of the elements of constructive stories.